2010
DOI: 10.1519/jsc.0b013e3181eccdf8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Speed and Agility Performance of College Football Players on Field Turf and Natural Grass

Abstract: The purpose of this study was to determine the difference in 40-yd dash and proagility times performed on field turf (FT) and natural grass (NG). Red-shirt freshmen National Collegiate Athletic Association Division II college football players (n = 24) performed 2 trials each of a 40-yd dash and proagility run on each surface. Sprints were timed by an electronic timing system (ET) and by 2 hand timers (HTs). Agility was timed on each surface by 2 HTs. There was no significant difference in 40-yd dash times betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 11 publications
4
55
2
2
Order By: Relevance
“…testing session 2: ICC = 0.69, 95% CI: 0.36 -0.90), and between-sessions (ICC = 0.66, 95% CI: 0.11 -0.90) reliability falling outside of the proposed threshold. These findings are contradictory to those from Stewart, et al [15], of whom found high intraday reliability (ICC = 0.9, 95% CI: 0.84 -0.94) for pro-agility within a sample of physical education students of similar ages to those of the present study (16.7 ± 0.6 years), and to those of Mayhew, et al [22], who concluded the pro-agility test to hold strong reliability Correlation Coefficient (ICC) with absolute agreement. This modality of ICC was used due to its capacity to detect absolute agreement within both rank and score.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…testing session 2: ICC = 0.69, 95% CI: 0.36 -0.90), and between-sessions (ICC = 0.66, 95% CI: 0.11 -0.90) reliability falling outside of the proposed threshold. These findings are contradictory to those from Stewart, et al [15], of whom found high intraday reliability (ICC = 0.9, 95% CI: 0.84 -0.94) for pro-agility within a sample of physical education students of similar ages to those of the present study (16.7 ± 0.6 years), and to those of Mayhew, et al [22], who concluded the pro-agility test to hold strong reliability Correlation Coefficient (ICC) with absolute agreement. This modality of ICC was used due to its capacity to detect absolute agreement within both rank and score.…”
Section: Discussioncontrasting
confidence: 99%
“…To the authors' knowledge, a small sample of literature to date has assessed the reliability and validity of both the modified t-test [23] and pro-agility [15,22] CODS tests, which are theorised to be applicable CODS assessments for youth tennis athletes [11]. However, this is the first study to evaluate the reliability (both within-and between-testing sessions) of the spider drill CODS assessment in comparison to other CODS assessments specifically within elite youth tennis athletes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial sprint performance has been shown to influence decrements in multi-sprint activity performance (Gaitanos, Williams, Boobis, & Brooks, 1993). Given that sprint times (Fletcher et al, 2009;Hughes et al, 2013) and agility actions (Gains, Swedenhjelm, Mayhew, Bird, & Houser, 2010;Hughes et al, 2013) can be faster on AT than NT, this may have implications for the fatigue response during or following match-play. The occurrence and severity of fatigue during soccer activity on artificial turf surfaces may be a concern as the risk of injury during a match is greatest during periods of fatigue (Greig & Siegler, 2009;Small, McNaughton, Greig, & Lovell, 2010).Using a 90 minute soccer simulation protocol to accurately replicate the movement patterns and physiological demand of soccer, Hughes et al (2013) reported that heart rate, blood lactate accumulation, as well as decrements in sprint and agility performances were not different between a NT and a third-generation AT.…”
Section: Introductionmentioning
confidence: 99%